What lies beneath: the complex nature of appointing women judges in Zambia and South Africa - Masengu, Tabeth Lynn (Department of Public Law, 2020)
Using a socio-legal framework, this thesis addresses the present dearth of research on gender and judging in Africa, by examining the judicial appointment processes in Zambia and South Africa. This study is grounded in the argument that judges, and those who appoint them, are operating in environments where multiple factors can and do have an impact on whether a country is able to successfully create a gender-diverse judiciary. Using a feminist lens, this thesis describes women in terms of gender and explores various facets of the appointment system, in order to respond to the research question. How do aspects of the judicial appointment process inform equal representation of women and men on the bench? Drawing from existing literature on gender and judging, this thesis interrogates particular formal and informal aspects of the appointment process. It highlights the various subtleties that exist within or around these aspects and how they affect women candidates, while appreciating the difficult balance that is involved in selecting judges. In doing so, this thesis affirms the importance of context when studying judicial appointments and seeking solutions for judicial diversity. This thesis additionally reveals various elements of the process affected by bias, discrimination, exclusion, and a traditional definition of merit, that invariably devalues women's contributions and attributes. This study makes the case for gender diversity not just in the courts but on the judicial appointment bodies that appoint judges. While arguing that one benefit of this diversity would be the presence of more representative perspectives, it acknowledges that a feminist perspective can and should also be held by male judicial appointers. This study makes suggestions for improving the appointment systems in both jurisdictions and emphasises the need for a multi-sector response.